Literature Review: Analysis on the Use of Wordwall as an Interactive Media in Elementary School Mathematics Learning (2020-2025) - Dewi, Najla' Ayuditiasni; Setiawan, Deni; Avrilianda, Decky; Ellianawati, Ellianawati (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to review various literature related to the development of interactive media using Wordwall in teaching integers at the elementary school level. The study employs a literature review method by analyzing relevant scientific articles, journals, and academic publications. Wordwall is a digital platform that allows teachers to create various types of interactive and engaging educational games. Based on the findings of the review, the use of Wordwall has been proven to enhance students' learning motivation, active participation, and understanding of integer concepts through a fun and non-monotonous approach. Moreover, this media provides a varied learning experience and promotes two-way interaction between teachers and students. However, several challenges arise in its implementation, such as limited access to technological devices, uneven internet connectivity, and the lack of teacher readiness in optimally utilizing technology in the learning process. The implications of this review highlight the importance of providing adequate training and mentoring for teachers, as well as sufficient infrastructure support, so that the use of interactive media like Wordwall can be effectively and sustainably integrated into mathematics learning in elementary schools.